Community building and early public relations : pioneer women's role on and after the Oregon trail - Pompper, Donnalyn, 1960- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"From the start, women were central to a century of westward migration in the U.S. Community Building and Early Public Relations: Pioneer Women's Role on and after the Oregon Trail offers a path forward in broadening PR's Caucasian/White male-gendered history in the U.S. Undergirded by humanist, communitarian, critical race theory, social constructionist perspectives, and a feminist communicology lens, this book analyzes U.S. pioneer women's lived experiences, drawing parallels with PR's most basic functions--relationship building, networking, community building, boundary spanning, and advocacy. Using narrative analysis of diaries and reminiscences of women who travelled 2,000+ miles on the Oregon Trail in the mid-to-late 1800s, Pompper uncovers how these women filled roles of Caretaker/Advocate, Community Builder of Meeting Houses and Schools, served a Civilizing Function, offered Agency and Leadership, and provided Emotional Connection for Social Cohesion. Revealed also is an inevitable paradox as Caucasian/White pioneer women's interactional qualities made them complicit as colonizers forever altering indigenous peoples' way of life. This book will be of interest to undergraduate and graduate PR students, PR practitioners, and researchers of PR history and social identity intersectionalities. It encourages us to expand the definition of PR to include community building and to revise linear timeline and evolutionary models to accommodate voices of women and people of color prior to the 20th century"--
Part I. Overview -- (Re)discovering the past for understanding public relations history today -- Re-examining the American west's lure and women's role representations -- Part II. Gendering and expanding roles as early public relations work -- Interrogating pioneer women's role as caretaker/advocate -- Exploring public relations from the care perspective: pioneer women's role as community builder of meeting houses and schools -- Civilizing function: pioneer women and religion -- Part III. Ideologies, women's work, and the 'female frontier' -- Understanding pioneer women's agency and leadership -- Expanding women's role: emotional connection for social cohesion theme and complicity -- Concluding thoughts and direction for discovering more women's voices for public relations history.
OCLC-licensed vendor bibliographic record.
Keywords: Women -- United States -- History -- 19th century; United States -- Territorial expansion; West (U.S.) -- History; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Public Relations; LANGUAGE ARTS & DISCIPLINES / Communication